Hierarchical Information Fault Diagnosis Method for Power System Based on Fireworks Algorithm - Haixun, Feng; Kenan, Yi; Zihang, Jia; Huijing, Bi (Distributed Generation & Alternative Energy Journal, 2021)
Power system fault diagnosis is an important means to ensure the safe and stable operation of power system. According to the specific situation of China’s current power grid automation level, a hierarchical fault diagnosis method based on switch trip signal, protection information and fault record- ing information is proposed. This method can not only diagnose simple fault and complex fault, but also judge fault type and phase, and complete fault location, which provides reliable guarantee for operators to quickly remove fault and resume operation. The diagnosis method based on this principle has good application effect in simulation test.